Islamicate Sexualities: The Artworks of Ebrin Bagheri - Gayed, Andrew (esse arts + opinions, 2017)
As a push against colonial forces and imperialism, homosexuality in the Middle East was historically made into an illegal identity category—one that, many argue, did not exist prior to increased contact with Western explorers and travellers. It is important to understand how the emergence of the Gay International coincided with that of Western gay sexuality studies. These issues are all at the forefront in the study of Islamicate sexualities. “Islamicate,” as defined by Marshal Hodgson, refers not directly,to the religion of Islam itself, but to the social and cultural complexities historically associated with Islam, including non-Muslims living within the same regions. Only by keeping imperialism at the forefront of the study of sexualities can we better situate how pre-modern Islamicate sexual scripts have resisted complete colonization and continue to exist in the diaspora.
Keywords: LGBTQIA2+; amériques; approches et analyses; arts; asie; canada; cours; discipline; féminisme islamique; har4600; histoire de l'art; iran; premier cycle; queer; ressource en ligne; régions géographiques; thématiques

91-LGBT+ - Babin, Sylvette; Glenn, Clinton; Gayed, Andrew; Barbu, Adam; Williamson, Andrea; Varghese, Ricky; Flavelle, Genevieve (2017)
Dans la foulée du numéro précédent, qui portait sur les féminismes, ce dossier poursuit la réflexion sur la question des genres et des sexualités en s’attardant aux pratiques et aux théories qui cherchent à transcender la pensée binaire de la société patriarcale hétéronormative et cisnormative. On y explore notamment les stratégies déployées par les artistes afin de rendre visible les communautés LGBT+ et de faire entendre la multiplicité des voix en marge du régime patriarcal de production des savoirs.
Keywords: 2000 à aujourd'hui; LGBTQIA2+; amériques; approches et analyses; arts; arts visuels et médiatiques; canada; corps; cours; discipline; har4600; histoire de l'art; hétérosexisme; premier cycle; périodes historiques; queer; québec; ressource en ligne; régions géographiques; sexualité; systèmes d'oppressions; thématiques; transféminisme